Efikasi Diri dan Pengaruhnya terhadap Prestasi Belajar Mahasiswa - Ika Wahyu Pratiwi; Hayati Hayati (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
During the undergraduate program, the undergraduate students are not separated from the academic and personal problems. There are students who can manage to overcome their problems and remain maintain their academic performance. One of the affecting factors is self efficacy. The purpose of this study is to find out if there is a significant influence between self-efficacy on the learning achievement of students in the class of 2016/2017 at Borobudur University. This research used a quantitative approach. The sample in this study was active undergraduate students of Borobudur University in 2016/2017 with a total of 120 students. The data analysis method in this study is linear regression. The results of this study show that there is an influence of self efficacy on the achievement of Borobudur University students in 2016/2017. The regression model test showed (Sig 0.00 < 0.05), with correlation coefficient values (R) in faculty students in the field of excretion amounting to 0.264, this suggests there is a common relationship between self efficacy variables and low learning achievement. Determination coefficient (R Square) in faculty students amounted to 0.070. This means that only 7% Â of variations in learning achievement can be explained by self efficacy variables, and the rest is influenced by other factors. Â Keywords: self-efficacy, learning achievement, students